Community for the friendless. Issue 8 (3rd August 2021) - Amnasan, Mike
ABSTRACT: In the San Francisco Bay Area Writing Community the addition of more writers provided an advantage: more venues and their services could be organized with additional people involved. The importance of more strangers coming into the community defied the usual means for gaining success as a writer through acquiring social connections within segregated groups of people who can provide advantages. People tend to prefer a small number of protagonists they can easily remember, not only in stories, but in journalism and history. If a researcher falls back on a small number of prominent writers to describe the writing community of the San Francisco Bay Area in the 80s and 90s, what was working will be erased from history, replaced by the familiar version of social movements lead by key figures. Something hard to sustain will be lost not only as a community, but as a way to imagine what's possible when greater numbers of participants are regarded as important and unlimited participation replaces gatekeepers. This will make participation easy and more comfortable even for people who aren't socially engaging, writers who can contribute to the writing community if social obstacles aren't put in their way.